NEOGAMES: A Serious Computer Game That Improves Long-Term Knowledge Retention of Neonatal Resuscitation in Undergraduate Medical Students - Hu, Liyuan; Zhang, Lan; Yin, Rong; Li, Zhihua; Shen, Jianqing; Tan, Hui; Wu, Jingyan; Zhou, Wenhao (Frontiers in Pediatrics, 2021)
Background: Serious games are potential alternatives for supplementing traditional simulation-based education for neonatal resuscitation training. However, evidence regarding the benefits of using serious games to improve long-term knowledge retention of neonatal resuscitation in undergraduate medical students is lacking. Objective: We designed a serious computer game "NEOGAMES" to train undergraduate medical students in neonatal resuscitation in a cost-friendly and accessible way and to examine whether serious game-based training improves long-term knowledge retention in medical students. Methods: "NEOGAMES" consists of a screen with images of an incubator, a baby, visual objects, anatomy, action cards, monitors, real-time feedback and emotional components. Undergraduate medical students from Shanghai Medical College of Fudan University were invited to participate and were allocated to a game group or a control group. Participants in the game group played the game before the training. All the participants completed three written tests, pre- and posttraining knowledge tests and a follow-up test after 6 months. Results: Eighty-one medical students participated in the study. The student demographic characteristics of the groups were comparable, including sex, age, and grade point average (GPA). Significant short-term knowledge improvement was noticed only for male students in the game group based on their 5.2-point higher test scores than those of the controls (p=0.006). However, long-term knowledge improvement at six months was identified for both male and female students in the game group, with test scores 21.8 and 20 points higher, respectively, than those of the controls (P<0.001). The long-term knowledge retention in the game group was almost 3 times higher than that in the control group.